2018
DOI: 10.1039/c7ta08629f
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic frameworks: efficient, metal-free, heterogeneous organocatalysts for chemical fixation of CO2 under mild conditions

Abstract: Covalent organic frameworks with hydroxy groups in the pore wall, which exhibit efficient, metal-free, heterogeneous catalytic performances for chemical fixation of CO2 under mild conditions, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
159
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(166 citation statements)
references
References 79 publications
6
159
0
1
Order By: Relevance
“…[27][28][29] These materials are constructedf rom organic building blocks through reversible covalent bonds. Bhanage and co-workers [39] and Liu and co-workers [40] demonstrated that hydrogen bond donors (HBDs), such as OH-decorated COF materials, could be used as excellentc atalysts for the chemicalf ixation of CO 2 to cyclic carbonate. [33][34][35][36] In recent years, COFs have been employed as heterogeneous catalysts for the cycloaddition of epoxides with CO 2 .F or example, Roeser et al [37] and Yu et al [38] reported that covalent triazine frameworks composed of ah igh number of basic nitrogen sites efficiently catalyzed the cycloaddition of CO 2 with different starting epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] These materials are constructedf rom organic building blocks through reversible covalent bonds. Bhanage and co-workers [39] and Liu and co-workers [40] demonstrated that hydrogen bond donors (HBDs), such as OH-decorated COF materials, could be used as excellentc atalysts for the chemicalf ixation of CO 2 to cyclic carbonate. [33][34][35][36] In recent years, COFs have been employed as heterogeneous catalysts for the cycloaddition of epoxides with CO 2 .F or example, Roeser et al [37] and Yu et al [38] reported that covalent triazine frameworks composed of ah igh number of basic nitrogen sites efficiently catalyzed the cycloaddition of CO 2 with different starting epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Covalent organic frameworks (COFs), [6][7][8][9][10] crystallinep orousm aterials formed by the self-assembly of purely organic building blocks, have been explored for aw ide range of applications, such as optoelectronics, [11][12][13] gas storage, [14] and catalysis. [15][16][17][18][19][20][21][22] COFs have also shown promise as adsorbents for organic dyes, [23][24][25][26][27] mercury, [28,29] radionuclides, [30] and lanthanides, [31] as carriers for drug delivery, [32][33][34] and isolation of industriallyr elevant compounds. [35] Recently, we demonstrated that COFs can be used to efficientlyc apture marine toxin okadaic acid from seawater.…”
mentioning
confidence: 99%
“…[193] COFs wurden als Katalysatoren fürdie Cycloaddition von CO 2 mit Epoxiden zu cyclischen Carbonaten entwi- ckelt. [194][195][196] So fçrdern COF-JLU7, [197] CTF-CSU auf Carbazolbasis [198] und CCTF-350 auf Imidazoliumbasis [199] (Abbildung 47 a-c) die Reaktion mit einer Ausbeute von 99 %unter Umgebungsbedingungen. Diese COFs sind effizienter als Homogen-und andere Heterogenkatalysatoren.…”
Section: Angewandte Chemieunclassified